Concepts and comments : A reader for students of English as a second language - Ackert, Patricia (New York : Holt, 1985)
This book assemes that the student has a 1000 word vocabulary. It is designed to teach another thousand words plus the reading skills of comprehension, finding the main idea, making inferences, and using context clues, prefixes, and suffixes to learn new words.
Keywords: English language; Concepts and comments; English language -- Textbooks for foreign speakers